COMPARATIVE FIQH ANALYSIS OF MAZHAB’S OF THOUGHT ON THE DISTRIBUTION OF ZAKAT TO NON-MUSLIM MUSTAḤIQ - Jauhari, Sofwan; Ghoni, Abdul (STAI Asy-Syukriyyah, 2025)
In an era marked by rapid global transformation, the study of Islamic legal methodology demands renewed scholarly attention. Contemporary challenges such as globalization, ethical finance, humanitarian crises, and minority rights require adaptive frameworks within Islamic jurisprudence capable of engaging complex modern realities. This study addresses the critical question of how classical uṣūl al-fiqh principles can be reconstructed to respond to these socio-economic and ethical challenges. Despite extensive scholarship on uṣūl theory, there remains a significant research gap in synthesizing classical doctrines with emerging contexts such as global zakat governance and the operational ethics of humanitarian aid. The main objective of this research is to develop a normative-constructive framework that bridges traditional fiqh reasoning with maqāṣid al-sharīʿah-based innovation, emphasizing practical relevance in contemporary legal interpretation. Employing a qualitative normative approach, the study critically examines epistemological shifts across major schools of thought and formulates a synthetic analytical model linking their methodologies. The novelty of this research lies in proposing a unified interpretive approach that repositions uṣūl al-fiqh as a dynamic and socially transformative discipline rather than a static textual system. The findings contribute to the broader discourse of Islamic legal renewal and open new directions for future research on integrative jurisprudence in addressing global ethical and governance issues.